Perilaku Konsumen terhadap Kebijakan PPN 12% dalam Perspektif Keadilan Pajak di Indonesia - Rahayu, Puji; Muttaqien, Zaenul (Journal of Business and Economics Research (JBE), 2025)
In early 2025, a 12% Value Added Tax (VAT) rate began to be implemented. Although this VAT rate only increased by 1% from the previous year's 11%, it has generated various perceptions among the public and industry. The public assumed the VAT rate increase would be followed by increases in the prices of other necessities. Furthermore, entrepreneurs also felt the impact of this VAT rate increase, fearing panic buying before the VAT rate increases and a decrease in consumer purchasing power after the VAT rate increases. The government has prepared several policies as alternatives. However, are these policies relevant to the concerns faced by consumers from various levels of society. The method used in this research is qualitative with secondary data analysis in the form of scientific articles. Articles were obtained using the Publish or Perish (PoP) tool, then the articles were presented in statistical form by the researcher. Furthermore, the findings of the literature review were used to analyze government policies, namely PMK 131 of 2024 and PMK 11 of 2025. The results of the study show that PMK 131 of 2024 and PMK 11 of 2025 strongly prioritize the principle of justice in VAT collection. VAT collection on non-luxury goods is subject to a rate of 12% multiplied by 1 1/12 of the selling or import price, while for luxury goods the collection is directly multiplied by 12% of the selling or import price. Therefore, it can be concluded that PMK 131 of 2024 is very relevant to address the problem of the VAT gap in collection and the increase in the 12% VAT rate does not impact consumers of non-luxury goods. Because the final result of this VAT collection according to the calculation formula is the same as being subject to a rate of 11%.